Activation of ferrate by carbon nanotube for enhanced degradation of bromophenols: Kinetics, products, and involvement of Fe(V)/Fe(IV). (1st June 2019) - Sun, Shaofang; Jiang, Jin; Qiu, Liping; Pang, Suyan; Li, Juan; Liu, Caihong; Wang, Lihong; Xue, Mang; Ma, Jun
Abstract: Very recently, several studies have found that homogeneous reducing agents (e.g., sodium thiosulfate (Na2 S2 O3 ), and sodium sulfite (Na2 SO3 )) can activate ferrate to enhance the degradation of selected contaminants. In this work, it was found that heterogeneous carbon nanotube (CNT) could accelerate ferrate (Fe(VI)) for the degradation of bromophenols (BrPs) of environmental concerns and alleviate the appearance of undesired by-products in effluent. Fe(VI) could react with BrPs over a wide pH range of 6–10 with apparent second-order rate constants of 1.8–1850 M −1 s −1 . Electrospray ionization-triple quadrupole mass spectrometry (ESI-QqQMS) analysis showed that dibrominated dihydroxylated biphenyls and dibrominated phenoxyphenols were possibly formed via coupling reaction of BrPs radicals generated from Fe(VI) oxidation through one-electron transfer. The presence of CNT could remarkably accelerate the degradation rates of BrPs by Fe(VI) in a wide pH range from 7 to 10. Moreover, the formed undesired polybrominated products during Fe(VI)/CNT oxidation were absorbed on CNT surface and thus removed from treated water. The Fe(VI)/CNT system was capable of selectively oxidizing electron-rich pollutants (e.g., BrPs, and sulfamethoxazole (SMX)), but reluctant to iopamidol (IPM) and nitrobenzene (NB). High-valent metal-oxo intermediates Fe(V)/Fe(IV) formed in situ from the reaction of CNT with Fe(VI) were likely responsible for this activation effect of CNT, which was further confirmed via using methyl phenyl sulfoxide (PMSO) as a probe compound. Comparatively, homogeneous reducing agent Na2 S2 O3 could enhance Fe(VI) degradation of BrPs at pH 7 and 8, while undesired polybrominated products were detected in effluent from Fe(VI)/Na2 S2 O3 system. These findings have crucial implications for the development of a promising oxidation process by combination of Fe(VI) and CNT for water and wastewater treatment. Graphical abstract: Image 1 Highlights: Fe(VI) could degrade bromophenols in a wide pH range. Undesired polybrominated products of concern were formed during Fe(VI) oxidation. CNT significantly accelerated the degradation of bromophenols by Fe(VI). The formed polybrominated products of concern were absorbed on CNT surface.